Clinical and laboratory characteristics of acute kidney injury in infants with diarrhea: a cross-sectional study in Bangladesh. Issue 1 (January 2020) - Shahrin, Lubaba; Sarmin, Monira; Rahman, Abu SMMH; Hasnat, Waliel; Mamun, Gazi MS; Shaima, Shamsun N; Shahid, Abu SMSB; Ahmed, Tahmeed; Chisti, Mohammod J
Objective: We described the clinical and laboratory characteristics of acute kidney injury (AKI) in infants with diarrhea. Methods: This medical record analysis was conducted in Dhaka Hospital of the International Centre for Diarrheal Disease Research Bangladesh from January to December 2015. Infants with elevated serum creatinine (>50 µmol/L) constituted cases (n = 146). We randomly selected 150 infants with normal creatinine levels as the controls. Both groups had diarrhea. Events occurring from admission to discharge were analyzed and compared to assess differences in characteristics of the groups. Results: Among the 146 patients with AKI, 130 (89%) were discharged after recovery. Logistic regression analysis, adjusting for potential confounders (such as oral rehydration salt intake at home, convulsions, abnormal mentation, and hypoxemia) showed that infants with AKI were independently associated with hypernatremia (odds ratio (OR) = 8.66, 95% confidence interval (CI) = 3.88–19.22), sepsis (OR = 4.71, 95% CI = 2.07–10.73), and severe dehydration (OR = 3.76, 95% CI = 1.78–7.95). Persistently elevated creatinine was associated with radiological pneumonia (OR = 2.16, 95% CI = 1.09–4.31) and sepsis (OR = 2.24, 95% CI = 1.14–4.40). Conclusion: Dehydration, sepsis, and hypernatremia were found to be associated with AKI in diarrheal infants. After proper correction of dehydration, persistently elevated creatinine could be associated with sepsis and pneumonia.